Correction: Corrigendum: Loess Plateau storage of Northeastern Tibetan Plateau-derived Yellow River sediment - Junsheng Nie (Nature Portfolio, 2016)
Nature Communications 6: Article number: 8511 (2015); Published: 9 October 2015; Updated: 18 February 2016. The original version of this Article contained errors in the Supplementary Information files: Zircon U-Pb age results for sample 23, shown in Supplementary Fig. 3, are incorrect, and missing from Supplementary Data 1, while several identification labels relating to Yellow River Lanzhou terraces samples are missing from Supplementary Data 2.